Vitamin D Management in Cutaneous Lupus Erythematosus: Balancing Photoprotection and Immunomodulation - Borowiecka, Patrycja; Węglarz, Aleksandra; Głuski, Jacek; Radziwonka, Agnieszka; Majszyk, Tomasz; Brzozowska, Agnieszka; Kosiorek, Paweł; Niezgoda, Ada; Olborska, Anna; Wrochna, Bartłomiej; et al. (Quality in Sport, 2026)
Background: Cutaneous lupus erythematosus (CLE) is an autoimmune inflammatory disorder which demands strict photoprotections, leading to vitamin D deficiency. This narrative review evaluates the interplay between vitamin D status, disease activity, and modern management challenges. Methods: A comprehensive literature search was conducted across PubMed, EMBASE, and Scopus databases for studies published up to January 2026, focusing on CLE, vitamin D metabolism, and clinical outcomes. Results: Vitamin D insufficiency is almost universal for all CLE patients. The etiology of this insufficiency is multifactorial, including therapy involving antimalarial agents, sun-avoidance, or sunscreen use. It correlates with higher disease activity, while supplementation significantly reduces Cutaneous Lupus Erythematosus Disease Area and Severity Index- Activity (CLASI-A) scores and shortens the duration of active skin lesions. Current 2026 vitamin D supplementation protocols for the general population may not be enough for CLE patients. Conclusions: Vitamin D should become an integral component of CLE management. Regular monitoring and individualized supplementation are crucial to overcome pharmacological and behavioral barriers. The chronological gap in existing literature suggests that there is a notable need for new randomized clinical trials that align with 2026 therapeutic standards. It would facilitate the development of supplementation protocols tailored to CLE patients.